Model-based Test Case Prioritization - Basa, S.S; Swain, S.K; Mohapatra, D.P (International Journal of Computer Sciences and Engineering, 2025)
The efficiency of Software testing can be improved by scheduling the test cases using test case prioritization technique (TCP). A novel test case prioritization approach is proposed to schedule the execution of test cases in testing process of software development. Our approach prioritizes the test cases generated from UML Sequence diagram. The major objective of our TCP approach is to achieve high rate of fault detection and test coverage. In this paper, an intermediate graph is created form UML sequence diagram to generate the message sequence paths. We calculate the weights of each node of the graph according to the affecting nodes using forward slice and edge using information flow model. Then the weights of test paths which are generated from sequence diagram are calculated by adding the weights of associated nodes and edges. According to the weights of corresponding test paths the test cases are prioritized. The obtained results indicate that the proposed technique is effective in prioritizing the test cases by the Average Percentage of Fault Detection (APFD) metric to estimate the performance of our proposed approach. The result of our proposed approach is compared with the result of traditional approach using APFD for some selected software. Finally, our proposed prioritization approach is also compared with some available related work